Determination of total scatter correction factor for non-square fields and fields with wedge - Ramly, Siti Aishah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
The aim of this study is to determine the total scatter correction factor for open and wedged rectangular fields for 6MV photon beam from Siemens :rvtX£2 linear accelerator. The total scatter factor, Scp consists of two components, the collimator scatter correction factor, Sc and phantom scatter correction factor, Sp. This study also determines for wedge factor of square and non-square fields from the same source. For open fields, measurements for Scp and Sc of square and non-square fields were carried out. The charge for each field size is normalized to the charge of 1 Ocm x 1 Ocm field size both obtained from the electrometer at 1 Ocm depth. Sc was measured in mini phantom in air while water phantom was for Scp measurement. The value of Sp is derived from the fonnula, Scp/Sc (1). To obtain the value of Sc, Scp and Sp for square and nonsquare fields of wedged fields, the procedure is the same as for the open fields. Subsequently, the wedge factor is obtained by taking the ratio of the charge when the wedge is inserted to the charge when the wedge is not inserted for each field size. For wedged field only 30 degrees wedge was utilized. The data shows that the total scatter correction factor for non-square fields both for the open and wedged fields are almost the same as the square fields for the field sizes investigated This would mean that Scp, Sc and Sp for non-square fields could be estimated by using the value of their equivalent square. The wedge factor for square fields and non-square fields agreed within 54% and 55%. Adding the wedge into the beam caused the value of total scatter correction factor to decrease by 54% and 55% compare to the open fields.